2021
DOI: 10.1186/s40645-020-00405-4
|View full text |Cite
|
Sign up to set email alerts
|

Marine microplastics as vectors of major ocean pollutants and its hazards to the marine ecosystem and humans

Abstract: Microplastic pollutes water, land, air, and groundwater environments not only visually but also ecologically for plants, animals, and humans. Microplastic has been reported to act as vectors by sorbing pollutants and contributing to the bioaccumulation of pollutants, particularly in marine ecosystems, organisms, and subsequently food webs. The inevitable exposure of microplastic to humans emphasises the need to review the potential effects, exposure pathways, and toxicity of microplastic toward human health. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(141 citation statements)
references
References 299 publications
2
97
0
6
Order By: Relevance
“…Just a few days before the lockdown, on March 7, 2020, 250 g were collected, but by September there was almost no plastic found (Supplementary Material Photo 1, lower panel). The impact of plastics on marine ecosystems is clearly recognized, e.g., (Santander-Rodriguez, 2017); Amelia et al (2021) have reviewed the impact of microplastic on marine ecosystems organism (food web). The range of plastics found is given in the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just a few days before the lockdown, on March 7, 2020, 250 g were collected, but by September there was almost no plastic found (Supplementary Material Photo 1, lower panel). The impact of plastics on marine ecosystems is clearly recognized, e.g., (Santander-Rodriguez, 2017); Amelia et al (2021) have reviewed the impact of microplastic on marine ecosystems organism (food web). The range of plastics found is given in the results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Quilliam et al (2020) and Randazzo et al (2020) have reported the COVID-19 virus in feces and domestic residual waters, and thus Larsen and Wigginton (2020), and Medema et al (2020) have proposed to correlate the presence of SARS-Coronavirus-2 RNA in Sewage with reported COVID-19. The impact from untreated wastewater on the marine environment and the whole trophic chain (Karen, 2019;Amelia et al, 2021) is a wellknown fact.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the analysis revealed a moderate level of variability of the trace metal contents among the three locations, as well as various types of MPs, which could, in principle, act as metal vectors. With respect to the latter point, various authors studied the relationship between trace metal contents and MPs in mussels and other bivalves, and concluded that MPs could act as metal ingress vectors [13,60,61]. However, some of them indicated that the entrance of Hg in mussels was facilitated due to the MPs, but the Hg elimination rate was also higher than in the case of other pathways [60,61].…”
Section: Trace Metal Contentsmentioning
confidence: 99%
“…They are also known for their bioconcentration ability, since they cannot regulate individual concentrations of metals [11] or other pollutants, for instance, MPs [9]. Moreover, different harmful contaminants, such as persistent organic pollutants (POPs) and trace metals, can be adsorbed on the MPs hydrophobic surface, so that MPs ingestion can contribute to higher uptake levels of other contaminants as well [8,12,13]. Thus, to identify the mussel exposure routes to a specific pollutant, it is important to analyze all possible vectors of the pollutant's specific uptake in the mussel tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation